A new species of Hyphessobrycon Durbin (Characiformes: Characidae) from the middle rio Sao Francisco and upper and middle rio Tocantins basins, Brazil, with comments on its biogeographic history - Dagosta, Fernando C. P.; Marinho, Manoela M. F. [UNESP]; Camelier, Priscila (Soc Brasileira Ictiologia, 2014)
A new species of Hyphessobrycon Durbin is described from tributaries of the rio Grande (rio Sao Francisco basin) draining east to the Serra Geral de Goias, of the rio Sao Domingos (upper rio Tocantins basin) and rio do Sono basins (middle rio Tocantins basin). Hyphessobrycon diastatos can be diagnosed from its congeners by the absence of humeral spot, 15-18 branched analfin rays, 1-3 maxillary conical to tricuspid teeth, a relatively well-defined dark caudal-peduncle spot, and elongation of dorsal- and anal-fin rays in mature males. The biogeographical significance of the distribution of the new species is evaluated and discussed.
Keywords: Adipose fin; Biogeography; Headwater capture; Serra Geral de Goias; Sexual dimorphism